"English as a tool for empowering women's educational success": A case study of a young rural Turkmen woman. Issue 1 (3rd July 2020) - Orazova, Gulshirin; Cohen, James
Abstract: English has gained in popularity as the world's lingua franca, inviting individuals and countries to join the international community. Since the collapse of the Soviet Union, the use of English has dramatically increased in Turkmenistan, in Central Asia (CA). Russian was required for securing jobs, professional development, and economic well‐being in CA countries during the time of the Soviet Union, but it has been replaced with English. Using liberal feminist theory (Groenhout, 2002; Tong, 2009) and Norton's (1995) investment theory, this case study examined the experience of one woman learning English as a foreign language in rural Turkmenistan and its role in her professional trajectory and identity development as an empowered Turkmen woman. The authors show how Ayna, the case study participant, invested in learning English as a child but was originally prohibited from postsecondary education by the family's matriarch because Ayna is female. Later, with help from her parents and an English tutor, Ayna used her advanced English skills to access postsecondary employment and education, where she was introduced to Western philosophical and sociological texts. Through these experiences Ayna transformed her identity as an empowered woman by increasing her awareness of gender inequality, shifted her perspectives on rural village life, and took on, as she said, "an English‐speaking mindset."